A mission divided : colonialism, race and culture in Fiji's Methodist Mission - Close-Barry, Kirstie (ANU Press, 2015)
This book provides insight into the long process of decolonisation within the Methodist Overseas Missions of Australasia, a colonial institution that operated in the British colony of Fiji. The mission was a site of work for Europeans, Fijians and Indo-Fijians, but each community operated separately, as the mission was divided along ethnic lines in 1901. This book outlines the colonial concepts of race and culture, as well as antagonism over land and labour, that were used to justify this separation. Recounting the stories told by the mission's leadership, including missionaries and ministers, to its grassroots membership, this book draws on archival and ethnographic research to reveal the emergence of ethno-nationalisms in Fiji, the legacies of which are still being managed in the post-colonial state today.